Awareness of Ecological Economics as a Model for Promoting Sustainable Construction - Oke, Ayodeji; Aigbavboa, Clinton; Ndou, Mpho (Journal of Economics and Behavioral Studies, 2017)
Construction industry is a major consumer of natural resources and this has a significant impact on the environment and socio-economic development of society. The result of this impact includes deforestation; climate change, air, water and land pollution; and the like. Ecological economics (EE) models are tools for assessing and understanding these issues with a view to enhancing green buildings and sustainable construction in general. As part of a continuous study, this research therefore examines the level of awareness of the concept of EE by construction professionals in a quest to adopting the principle of sustainable development. Data were collected through questionnaires administered on relevant and experienced construction professionals such as construction project managers, architects, engineers, quantity surveyors and construction managers. EE as an aid would help in mitigating construction impacts on the environment, thereby enhancing sustainability but it is barely practised in the construction industry. This is as a result of the fact that construction professionals have little or no knowledge of its existence in the local industry. Most professionals with knowledge of the concept in the study area obtained the information on sustainability through the media and short courses .. The basic influencing factors are related to professionals’ levels of education, the economic development of the country and knowledge of the environment. Introducing EE through communicating new ideas to stakeholders (through environmental campaigns, conferences, and the like) as well as incentivising ideas for change relating to greener construction will assist in overcoming the barriers to the adoption of EE in the construction industry. Professionals also need to keep abreast of current sustainable practices, their benefits, challenges, barriers as well as the methods of overcoming these barriers in their quest for delivering sustainable projects.